Chronic temporomandibular disorders are associated with higher propensity to develop central sensitization: a case–control study. Issue 5 (17th May 2023) - Cayrol, Timothée; van den Broeke, Emanuel N.; Gerard, Eve; Meeus, Mira; Mouraux, André; Roussel, Nathalie; Pitance, Laurent
Abstract : Compared with healthy subjects, patients with chronic temporomandibular disorders have a greater susceptibility to develop secondary mechanical hyperalgesia induced by high-frequency electrical stimulation. Abstract: Temporomandibular disorders (TMD) include a group of musculoskeletal disorders that may involve increased responsiveness of nociceptive neurons in the central nervous system (ie, central sensitization). To test this hypothesis further, this study examined whether, as compared with healthy subjects, patients with chronic TMD have a greater propensity to develop secondary mechanical hyperalgesia—a phenomenon that can be confidently attributed to central sensitization. In this case–control study, we assessed the area of secondary mechanical hyperalgesia induced experimentally by delivering high-frequency electrical stimulation (HFS) to the volar forearm skin in 20 participants with chronic TMD and 20 matched healthy controls. High-frequency electrical stimulation consisted in 12 trains of constant-current electrical pulses (5 mA) delivered at 42 Hz. The area of secondary mechanical hyperalgesia was evaluated 30 minutes after applying HFS. The area of secondary mechanical hyperalgesia induced by HFS was on average 76% larger in the chronic TMD group (M = 67.7 cm 2, SD = 28.2) than in the healthy control group (M = 38.4 cm 2, SD = 14.9; P = 0.0003). Regarding secondary outcomes, there was no group difference in the intensity of secondary mechanical hyperalgesia, but allodynia to cotton after HFS was more frequent in the chronic TMD group. To the best of our knowledge, this is the first study to show that individuals with chronic TMD have an increased propensity to develop secondary hyperalgesia in a site innervated extratrigeminally. Our results contribute to a better understanding of the pathophysiology of chronic TMD.